2019
DOI: 10.1016/j.biomaterials.2019.04.014
|View full text |Cite|
|
Sign up to set email alerts
|

On-site fabrication of Bi-layered adhesive mesenchymal stromal cell-dressings for the treatment of heart failure

Abstract: Mesenchymal stromal/stem cell (MSC)-based therapy is a promising approach for the treatment of heart failure. However, current MSC-delivery methods result in poor donor cell engraftment, limiting the therapeutic efficacy. To address this issue, we introduce here a novel technique, epicardial placement of bi-layered, adhesive dressings incorporating MSCs (MSC-dressing), which can be easily fabricated from a fibrin sealant film and MSC suspension at the site of treatment. The inner layer of the MSC dressing, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Human AMSC were generated as previously described 12 . Amniotic membranes procured following cesarean section of pregnant females were treated with collagenase and dispase (Sigma Aldrich, MO, USA) 10 , 12 . Human BMSC from healthy donors were purchased from AllCells (CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human AMSC were generated as previously described 12 . Amniotic membranes procured following cesarean section of pregnant females were treated with collagenase and dispase (Sigma Aldrich, MO, USA) 10 , 12 . Human BMSC from healthy donors were purchased from AllCells (CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the immunomodulatory characteristics of mesenchymal cells within fetal membranes play key roles in fetal-maternal tolerance 9 . Several recent studies reported that human amnion-derived MSC (AMSC) exhibited therapeutic efficacy in rodent disease models including colitis induced by chemicals 10 , 11 , heart failure induced by coronary artery ligation 12 , and allo-GVHD 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This work showed that the adhesive matrix can promote MSCs’ function and the technique enhanced cardiac function recovery with improved myocardial tissue repair in a rat ischemic cardiomyopathy model. [ 351 ]…”
Section: Emerging Applications Of Tissue Adhesivesmentioning
confidence: 99%
“…Traditional scaffold-based tissue engineering strategies employ a cytocompatible, biodegradable and mechanically stable natural or synthetic in origin polymeric scaffold with a fully interconnected porous network for efficient transport and exchange of oxygen, nutrients and metabolites 13 , 14 . Although very many scaffold conformations (e.g., hydrogels 15 , 16 , sponges 17 , 18 , fibres 19 , 20 , films 21 , 22 ) have been developed, and have demonstrated safety and efficacy in preclinical setting and phase I clinical trials as cell delivery vehicles, only a handful of them constitute a Food and Drug Administration (FDA)/European Medicines Agency (EMA) approved device (Table 1 ). This limited technology transfer from laboratory benchtop to clinical applicability has been attributed to component (e.g., limited understanding of the mechanism of action of the various device components; device components do not comply with regulatory frameworks; toxicity issues) and process (e.g., too complex to allow for large-scale efficient and reproducible manufacturing; too long to be profitable) limitations.…”
Section: Introductionmentioning
confidence: 99%